2017
DOI: 10.3390/w9050315
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Precipitation and Topography on Total Phosphorus Loss from Purple Soil

Abstract: Abstract:The Sichuan Basin is the main agricultural production area of the upper reaches of the Yangtze River and is also an extremely important ecological area because it is rich in biodiversity and has complex and diverse landscape types. The dominant soil type, purple soil, is prone to rapid soil erosion and weathering processes because it is shallow and rich in phosphorus and other nutrients. Field experiments were conducted to reveal the effects of precipitation and topography characteristics on nonpoint … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The amount of phosphate fertilizer applied in Shigatse was 1.50-2.37, 2.86-5.63, and 7.03-7.48 times that in Lhasa, Shannan, and Nyingchi, as listed in Table 4. The ability of P to enter water from surface sources is affected by vegetation cover, soil type, river slope, and other factors [35][36][37]. The diversity index of plant from the northwest to the southeast on the mainstream increases from 44.40 to 125.23, the biomass increases from 2.07 t/hm 2 to 106.01 t/hm 2 , the NDVI increases with the rate of 0.1 to 0.6, the soil erosion decreases gradually, and the ecology is gradually improving [38][39][40].…”
Section: Influencing Mechanism Of Spatial Distributionmentioning
confidence: 99%
“…The amount of phosphate fertilizer applied in Shigatse was 1.50-2.37, 2.86-5.63, and 7.03-7.48 times that in Lhasa, Shannan, and Nyingchi, as listed in Table 4. The ability of P to enter water from surface sources is affected by vegetation cover, soil type, river slope, and other factors [35][36][37]. The diversity index of plant from the northwest to the southeast on the mainstream increases from 44.40 to 125.23, the biomass increases from 2.07 t/hm 2 to 106.01 t/hm 2 , the NDVI increases with the rate of 0.1 to 0.6, the soil erosion decreases gradually, and the ecology is gradually improving [38][39][40].…”
Section: Influencing Mechanism Of Spatial Distributionmentioning
confidence: 99%
“…The Sichuan Basin, with its rich biodiversity and complex landscapes in southwestern China, is the main agricultural production region in the upper reaches of the Yangtze River [1]. The primary soil type in this region is purple soil, which is often neutral or alkaline [2]; rich in mineral nutrients [3]; and prone to weathering, erosion, and leaching [4].…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the effects of crop residue removal on the purple soil properties and productivity, we conducted an on-farm experiment in purple regions and used the RUSLE 2 model to simulate soil erosion under various residue removal levels. The objectives of this study were (1) to explore the impact of different crop residue removal rates on the soil chemical properties and erosion loss, (2) to assess the soil productivity by measuring crop yields under different residue removal conditions, and (3) to determine the maximum residue removable rate in the researched area.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the source apportionment of phosphorus at the watershed scale is critical for regional management [7,8]. Previous studies have identified that non-point sources provide the main contribution of phosphorus to the Yangtze and its tributary [3,9,10]. To characterize indirect, multiple and dynamic non-point sources, it is common to use suitable modeling tools for the estimation of phosphorus flux and source apportionment [11][12][13].…”
Section: Introductionmentioning
confidence: 99%